A review of open source discrete event simulation software for operations research. Issue 3 (1st August 2016) - Dagkakis, G; Heavey, C
Abstract: This article reviews the state of the art in Open Source (OS) Discrete Event Simulation (DES) software used for decision support in Operations Research (OR) focusing on the modelling of manufacturing, services, supply chain management and logistics. DES is arguably one of the most popular OR techniques. Commercial-Off-The-Shelf (COTS) DES software has been around for decades and it has considerably helped in the wider adoption and use of DES, providing the user with tools for modelling, debugging and experimentation. However, such tools often have limitations regarding their aspects such as cost, flexibility and reusability and OS DES seems to be a strong alternative in order to fill those gaps. The scope of our review is to present the state of the art in OS DES and identify future areas of research. The paper concludes with the desired features that an OS DES project should have in order to become a notable competitor against COTS equivalents in the OR domain.